Cortical thickness deviations as biomarker for subtyping and prognosis in pediatric brainstem tumors - Heyuan Jia; Kaikai Wang; Peng Zhang; Mingxin Zhang; Yiying Mai; Congying Chu; Xuntao Yin; Lingzhong Fan; Liwei Zhang (Scientific Reports)
Abstract Brainstem tumors exert profound effects on cortical organization and functionality across the whole brain. However, the precise implications of changes in cortical thickness (CTh) for patient stratification and prognostic assessment remain unclear. Our study seeks to address these gaps and provide clearer insights into the distant impact of brainstem tumors. This study involved 124 pediatric patients with brainstem tumors and 849 healthy controls. Using CAT12 segmentation on 3D T1-weighted MRI scans and Gaussian process regression modeling, we established a normative CTh model from healthy data. CTh deviations of patients were quantified and clustered, revealing two distinct subtypes: Subtype 1 with extremely positive deviations and Subtype 2 with extremely negative deviations, correlating with better survival. Kaplan-Meier analysis confirmed significant survival differences between these subtypes. Additionally, a greater number of brain regions with positive CTh deviations was found to correlate with larger tumor volumes. These findings suggest that CTh deviation is a non-invasive imaging marker, facilitating patient subtyping and survival prediction. These insights equip clinicians to tailor treatment plans and establishes a valuable precision medical tool for clinical evaluation and monitoring.